2006
DOI: 10.1007/s10495-006-9527-8
|View full text |Cite
|
Sign up to set email alerts
|

Clearance of apoptotic and necrotic cells and its immunological consequences

Abstract: The ultimate and most favorable fate of almost all dying cells is engulfment by neighboring or specialized cells. Efficient clearance of cells undergoing apoptotic death is crucial for normal tissue homeostasis and for the modulation of immune responses. Engulfment of apoptotic cells is finely regulated by a highly redundant system of receptors and bridging molecules on phagocytic cells that detect molecules specific for dying cells. Recognition of necrotic cells by phagocytes is less well understood than reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
264
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 295 publications
(270 citation statements)
references
References 193 publications
3
264
0
3
Order By: Relevance
“…We showed that apoptotic cells are engulfed by a zipper-like mechanism of phagocytosis ( Figure 1), whereas necrotic cells are internalized by a macropinocytotic mechanism, such that parts of the cell are co-ingested together with extracellular fluid. 8,31,32 In contrast with the initial paradigm, PS exposure mediates recognition and engulfment not only of apoptotic cells, but also of necrotic cells 33,34 and of cells dying from autophagic cell death, 35 indicating that PS-mediated clearance may be a general mechanism irrespective of the way a cell dies. Accordingly, several macrophage receptor systems known to be involved in the engulfment of apoptotic cells also contribute to the uptake of necrotic cells.…”
Section: Positive Regulators Of Uptake Dying Cellmentioning
confidence: 97%
See 3 more Smart Citations
“…We showed that apoptotic cells are engulfed by a zipper-like mechanism of phagocytosis ( Figure 1), whereas necrotic cells are internalized by a macropinocytotic mechanism, such that parts of the cell are co-ingested together with extracellular fluid. 8,31,32 In contrast with the initial paradigm, PS exposure mediates recognition and engulfment not only of apoptotic cells, but also of necrotic cells 33,34 and of cells dying from autophagic cell death, 35 indicating that PS-mediated clearance may be a general mechanism irrespective of the way a cell dies. Accordingly, several macrophage receptor systems known to be involved in the engulfment of apoptotic cells also contribute to the uptake of necrotic cells.…”
Section: Positive Regulators Of Uptake Dying Cellmentioning
confidence: 97%
“…For example, C1q, mannose-binding lectin, pentraxin-3, C3, C4, C-reactive protein (an acute phase protein), and thrombospondin bind predominantly to late apoptotic or secondary necrotic cells. 8 Great progress has been achieved during the last decade in unraveling molecules on the surface of apoptotic cells, but it is still not clear how non-apoptotic cells, namely necrotic and autophagic cells, are recognized by macrophages. We showed that apoptotic cells are engulfed by a zipper-like mechanism of phagocytosis ( Figure 1), whereas necrotic cells are internalized by a macropinocytotic mechanism, such that parts of the cell are co-ingested together with extracellular fluid.…”
Section: Positive Regulators Of Uptake Dying Cellmentioning
confidence: 99%
See 2 more Smart Citations
“…Electroporation has been used to transfer plasmid DNA into monocytic cell lines or macrophages with high efficiency (Weir and Meltzer, 1993;Hume et al, 2001). Usually, electroporation causes significant cell death and release of intracellular contents, which is known to induce macrophage responses (Krysko et al, 2006). Moreover, both transfection and electroporation with plasmid DNA containing unmethylated CpG (cytosine followed by guanine) dinucleotides may activate macrophages through Toll-like receptor (TLR)-9 to produce proinflammatory cytokines (Stacey et al, 1996;Sester et al, 1999;Jiang et al, 2006).Thus, the existing methods of plasmid delivery perturb the normal physiological status of the macrophage population and complicate interpretation of the experimental data.…”
Section: Introductionmentioning
confidence: 99%